ANALISA DAN PERANCANGAN SISTEM PENGHITUNG ZAKAT - Setiawati, Popong (Lembaga Penerbitan Universitas Esa Unggul, 2019)
Technology is increasingly advancing and developing. There are a lot of internet services and a special bureaucracy where zakat is paid, but can everyone enjoy internet service? And do all people believe in bureaucracy? Sometimes in addition to the high cost of the internet, a sense of unbelief in this bureaucracy is an obstacle for those who want to check how much zakat they are required to pay, which is an obligation of Muslims to issue zakat for those who are already narrated as described in the Qur'an. and al-Hadith, to regulate expenditure and distribution of the property of the people and its distribution. The difficulty to calculate zakat independently or individually, because they do not yet understand the calculation of zakat, especially the calculation of zakat for animal products. In Scientific Writing, the author tries to make an analysis and design of Zakat Calculation System as one solution.The writing method used in the design uses a flowchart diagram that illustrates the flowchart outlining the stages in solving a problem as outlined in the form of an algorithm. This application program is still limited to the design of flowchart diagrams that do not use the application programming language. The results of this study can be concluded that the analysis and design of the flow diagram of the zakat calculation system can provide information about the steps of the zakat calculation system flowchart and help the calculation process that is accurate and precise as well as the prototype for the application to be applied so that it is easy to use by users with very interactive .Ã‚Â Keywords: Zakat, Flowcharti, Story Board